Flexible Zinc–Air Batteries with Ampere‐Hour Capacities and Wide‐Temperature Adaptabilities. Issue 13 (17th February 2023) - Zhong, Xiongwei; Zheng, Zhiyang; Xu, Jiahe; Xiao, Xiao; Sun, Chongbo; Zhang, Mengtian; Ma, Jiabin; Xu, Baomin; Yu, Kuang; Zhang, Xuan; Cheng, Hui‐Ming; Zhou, Guangmin
Abstract: Flexible Zn–air batteries (FZABs) have significant potentials as efficient energy storage devices for wearable electronics because of their safeties and high energy‐to‐cost ratios. However, their application is limited by their short cycle lives, low discharge capacities per cycle, and high charge/discharge polarizations. Accordingly, herein, a poly(sodium acrylate)–polyvinyl alcohol (PANa–PVA)–ionic liquid (IL) hydrogel (PANa–PVA–IL) is prepared using a hygroscopic IL, 1‐ethyl‐3‐methylimidazolium chloride, as an additive for twin‐chain PANa–PVA. PANa–PVA–IL exhibits a high conductivity of 306.9 mS cm −1 and a water uptake of 2515 wt% at room temperature. Moreover, a low‐cost bifunctional catalyst, namely, Co9 S8 nanoparticles anchored on N‐ and S‐co‐doped activated carbon black pearls 2000 (Co9 S8 ‐NSABP), is synthesized, which demonstrates a low O2 reversibility potential gap of 0.629 V. FZABs based on PANa–PVA–IL and Co9 S8 ‐NSABP demonstrate high discharge capacities of 1.67 mAh cm −2 per cycle and long cycle lives of 330 h. Large‐scale flexible rechargeable Zn–air pouch cells exhibit total capacities of 1.03 Ah and energy densities of 246 Wh kgcell −1 . This study provides new information about hydrogels with high ionic conductivities and water uptakes and should facilitate the application of FZABs in wearable electronics. Abstract : An ionic liquid (IL) additive hydrogel is reported for flexible Zn–air batteries (FZABs). Similar to a crab, the IL creates pores and captures water in the hydrogel, which improves the ionic conductivity and water retention of the hydrogel. The FZABs based on this hydrogel can operate at high and low temperatures.